GENDER EQUALITY AS A GUARANTEE OF A SUSTAINABLE SOCIETY: AN ANALYTICAL STUDY BASED ON UZBEKISTAN‘S EXPERIENCE - Shahnoza Kamoliddin qizi Ortiqboyeva,; M.M. Inagamova, (PEDAGOGS, 2025)
Abstract: This article explores the role of gender equality in building a sustainable society, with a focus on Uzbekistan’s legal reforms and institutional efforts. Drawing on theoretical frameworks and practical developments, the study analyzes how gender parity contributes to social justice, economic growth, and political inclusivity. The findings suggest that ensuring gender equality is not only a human rights imperative but also a strategic pathway to long-term societal resilience.